FORMATION OF THE PROFESSIONAL COMPETENCE OF STUDENTS FUTURE TEACHERS OF VOCATIONAL TRAINING IN THE SYSTEM OF HIGHER EDUCATION ON KAZAKHSTAN - Zhanguzhinova, Meruyert (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The current stage of the reform of higher professional education imposes entirely new requirements for innovative renewal, content, methods and the development of professional competence of future teachers of Vocational training in Cloth Design specialization.The article analyzes the relevant aspects of the formation of professional competence of future teachers of fashion design, based on the thesis: "Formation of professional competence of future teachers Vocational training in the higher education system in Kazakhstan" for the degree of doctor of pedagogical sciences, which is being developed in Rezekne Technological Academy (Latvia) under the direction of doctor of pedagogical sciences, Professor Velta Lubkina.